Perspectives on Reconstruction - Streissguth, Thomas, 1958- (Perspectives on US history., 2018)
Examines different perspectives on Reconstruction in the American South after the Civil War. Explores important figures, key developments, and its lasting impact. Provides facts, statistics, critical thinking questions, illustrations, a glossary, and further resources.